Scope of mechanical harvesting of Saffron for economic development of farmers in Kashmir Region of Jammu & Kashmir, India - Kumar, Vinay; Nirbhavane, Sawati; Parihar, Neeraj Singh (Indian Journal of Hill Farming, 2019)
Saffron a perennial herb, well-known for its aroma and used for flavouring, is a culinary delight. It is an important commodity and is of great significance in the agricultural economics of Jammu and Kashmir. Saffron is popularly known as Red Gold. The commercial part of saffron is Stigma. Saffron is used in industries like food, pharmaceutical, cosmetic and perfumery as well as in the textile dyes. In India most of the saffron production is limited to the state of Jammu and Kashmir. Besides, having tremendous medicinal values, saffron has traditionally been associated with the famous Kashmir cuisine and undoubtedly represents the rich cultural heritage of Kashmir. This legendry crop is under threat of extinction and warrants collective attention of Mechanisation, researchers, farmers and policy makers. In the production process of Saffron spice, flower harvesting and stigma separation are the most challenging phases of the entire process. In this paper, mechanical devices for supporting the human work inharvesting and field tests are provided, presented and described as well. The harvesting device described has a simple design and is capable of performing the cutting procedure with only one actuated degree of freedom.